Annual effective dose of radon due to exposure in indoor air and groundwater in Bathinda district of Punjab. Issue 5 (August 2016) - Mehra, Rohit; Kaur, Kirandeep; Bangotra, Pargin
In the present study, an attempt has been made to estimate the actual dose received by the residents due to their exposure to indoor radon, indoor thoron and radon concentration in water of Bathinda district of Punjab considering the different factors like dissolution of gases in blood and contribution of waterborne radon in increasing indoor radon levels following various protocols set up by the United States Environmental Protection Agency. The calculated values have shown a good positive correlation (R 2  = 0.80) between indoor radon concentration and concentration of radon gas in soil in Bathinda district of Punjab, India. The correlation has been successfully established by using alpha spectrometry technique. Along with this, another linear relationship has also been established between indoor radon concentration and indoor thoron concentration keeping site conditions constant. The ratio of indoor thoron concentration to indoor radon concentration ranges from 0.68 to 1.53 with an average value of 1.10 which indicates that thoron contribution is not negligible in comparison to radon and hence its measurements cannot be neglected. The annual effective dose contributed due to inhalation of radon is 0.86 mSv and due to thoron is 0.96 mSv which is lower than the world average value of annual effective dose reported by the United Nations Scientific Committee on the Effects of Atomic Radiation, 2000.